Features of the growth of the English oak provenances in Vinnytsia region - Смашнюк , Л. В. (Forestry and Forest Melioration, 2022)
Introduction For more than a century, provenance tests have been a reliable and valid tool for studying the intraspecific variability of forest tree species. They also play an important role in the conservation of forest genetic resources ex situ. The establishment and research of English oak (Quercus robur L.) provenance tests in Ukraine have been carried out since the beginning of the 20th century. During this period, nine plots of oak provenance tests have been created with 174 provenances represented there. Based on the studies of the provenance tests, a forest seed zoning for the main forest-forming tree species of Ukraine was developed, as a result of which nine forest seed regions and six sub-regions were allocated for English oak. The aim of the study was to assess the prospects and growth success for the English oak proveniences in the Vinnytsia region conditions. Materials and Methods We studied the English oak provenance tests created in the spring of 1964 in district 20 of the Tyvriv Forestry in the Vinnytsia Forest State Enterprise, under the leadership of D. Lavrynenko and V. Porva. The plot involves 65 proveniences from 10 climate regions, 17 forest seed regions and 20 sub-regions. We used three indicators to evaluate how English oak proveniences respond to growing conditions: their viability, average height and diameter. The viability of proveniences was determined as a percentage of the initial number of trees planted in the blocks. The growth indicators were determined in accordance with methods generally accepted in forest mensuration. A modified method developed by M. Merzlenko, based on the IUFRO methodology, was used to calculate the introduction expedience indicator. Statistical calculations were performed using Microsoft Excel. Results The viability of the control variant was 9.7%. The study also showed that the most viable variants are Gantsevichi from Belarus (14.3%), Ogre from Latvia (13.7%) and Golovanivsk from Ukraine (13.1%). The weakest variant is Novocheremshansk from RF (4.0%). The average height of the studied oak proveniences varied from 18.3 to 22.1 m; the average diameter was from 20.6 to 27.2 cm. However, according to the t-test, with 95% confidence, only four proveniences exceeded the height of the control. They are Velizh (number 14), Chekalin (number 37), Cherven (number 52), and Bezhitsa (number 64). According to the average diameter, no significant excesses were found. The coefficient of individual variability within proveniences ranged from 2.8 to 22.4% in height and from 15.4 to 31.6% in diameter. The expediency index of the introduction of English oak proveniences ranged from -2.75 (Novocheremshansk number 57) to +0.30 (Bezhitsa number 64). Five variants were included into the promising group (G = +0.2 and higher): Bezhitsa, Starokostyantyniv, Trostyanets, Cherven and Golovanivsk. Conclusions The assessment of the viability and growth of English oak proveniences carried out in the provenance tests in Vinnytsia Forest State Enterprise revealed the prospects of using seeds from Khmelnytsk, Sumy, and Kirovohrad regions of Ukraine, Minsk region of Belarus, and Briansk region of RF in the reforestation and afforestation of Vinnytsia region. The best results of growth and viability were recorded in eastern (Ulyanovsk region of RF, Bashkiria, Chuvashia, Tatar ASSR) and northwestern (Estonia, Lithuania, Latvia, Leningrad region) proveniences. 1 Fig., 3 Tables, 21 Refs.